2012
DOI: 10.2147/ijn.s32648
|View full text |Cite
|
Sign up to set email alerts
|

Study on antibacterial alginate-stabilized copper nanoparticles by FT-IR and 2D-IR correlation spectroscopy

Abstract: Background:The objective of this study was to clarify the intermolecular interaction between antibacterial copper nanoparticles (Cu NPs) and sodium alginate (NaAlg) by Fourier transform infrared spectroscopy (FT-IR) and to process the spectra applying two-dimensional infrared (2D-IR) correlation analysis. To our knowledge, the addition of NaAlg as a stabilizer of copper nanoparticles has not been previously reported. It is expected that the obtained results will provide valuable additional information on: (1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
59
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(68 citation statements)
references
References 63 publications
8
59
0
1
Order By: Relevance
“…The modification of the shape of the CeH stretching in the range from 1450 to 1210 cm À1 also indicates the interaction with copper [32]. According to these findings it can be concluded that FTIR spectroscopy provided clear evidence of copper incorporation in hydrogels.…”
Section: Structural Propertiesmentioning
confidence: 62%
See 1 more Smart Citation
“…The modification of the shape of the CeH stretching in the range from 1450 to 1210 cm À1 also indicates the interaction with copper [32]. According to these findings it can be concluded that FTIR spectroscopy provided clear evidence of copper incorporation in hydrogels.…”
Section: Structural Propertiesmentioning
confidence: 62%
“…The in vitro antimicrobial properties of CI and CR hydrogel samples were evaluated according to the described procedure [32]. The percentage of inhibition of CI and CR samples was calculated in relation to the hydrogel samples without copper (H0 and H7).…”
Section: Antimicrobial Propertiesmentioning
confidence: 99%
“…Larger the surface area ensures an increased range of interaction with bio-organic material present on the viable cell surface. These synthesized nanomaterials are designed and engineered for incorporation into consumer products (Diaz, 2012;Kahrilas, 2014). The antimicrobial activities of synthesized nanoparticles for example CuO, ZnO, TiO2, SiO2 etc.…”
Section: Introductionmentioning
confidence: 99%
“…This development had compelled clinicians to rely on in vitro antimicrobial susceptibility testing for diagnostic purposes. 4 In this regard, synthesis or extraction of compounds such as nanoparticles with antimicrobial properties is essential, and has potentially promising applications in the fight against the ever-growing number of antimicrobial-resistant pathogenic microorganisms which pose a continuous threat to human and animal health.…”
Section: Introductionmentioning
confidence: 99%